Calibration of the Discrete Element Method and Modeling of Shortening Experiments - Li, Changsheng; Yin, Hongwei; Wu, Chuang; Zhang, Yingchun; Zhang, Jiaxing; Wu, Zhenyun; Wang, Wei; Jia, Dong; Guan, Shuwei; Ren, Rong (Frontiers in Earth Science, 2021)
The discrete element method (DEM) is becoming widely accepted as an effective method of addressing tectonic problems in granular materials. It is capable of reproducing structures observed in the analogue model (AM). However, the previous experiments also pointed to variability among DEM and AM models in the number of fault zones, the dip angle and spacing, and in the evolution of surface slope of thrust wedge. The accuracy of DEM depends on the input parameter values, so the calibration of the discrete element method is very important. Microscopic properties of particles and macroscopic properties of loose quartz sand were calibrated through a series of repose angle and biaxial tests. Furthermore, an AM was constructed to simulate the evolution of the thrust wedge to compare with DEM results. DEM and AM results indicate an encouraging overall agreement in model evolution. Based on a new automated wedge quantification method, DEM results were systematically compared with AM in the number of fault zones, their dip angle and spacing, the evolution of surface slope of thrust wedge, and other parameters. Our study provides a necessary comparison between commonly applied modeling approaches, which is important for more confidently applying these methods to understand real fold and thrust belt systems.